Design and fabrication of automatic flour filter and separator - Zainal Abidin, Nurrul Amilin; Michael, Zeno; Mohd Yusri, Muhammad Amir Haziq (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
The process of filtering flour to finish often leads to energy and time consuming, especially for large scale business. The flour filters sieve traditionally used are made of wood, plastic, and metal, which are susceptible to corrosion and contamination over time. The traditional flour filter sieve used in household is however small, and thus can strain up to certain amount of flour. The flour filter machine available in the market howbeit, is technically bulky, non-portable, and expensive. The aim of this project is to design and fabricate a medium-sized, portable, and affordable flour filter machine that can sift the flour for home appliances as well as small scale business purposes. The proposed automatic flour filter and separator machine is equipped with an AC motor that powers the conveyor which is responsible to move the filter repeatedly in linear direction. The sifted flour will go into a funnel equipped on the lower part of the filter. This machine is useful for the home appliances, small and even large-scale business that uses flour as a main ingredient. The machine is portable, considerable lightweight, and is designed to reduce the energy and the time consumed in filtering the flour.